2023
DOI: 10.1002/adem.202201838
|View full text |Cite
|
Sign up to set email alerts
|

Gradient Origami Metamaterials for Programming Out‐of‐Plane Curvatures

Abstract: Designer materials, where rationally designed geometry at the small scale gives rise to unusual materials properties at the macro-scale, are often called metamaterials. [1][2][3][4][5][6] Origami structures are a traditional Japanese art, which have recently found their way into metamaterials research due to their powerful capability to transform flat 2D structures into complex 3D structures along their creases. [7] Particularly, Miuraori origami, also known as herringbone geometry (Figure 1a,b), has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…17 It is recently known that the introduction of the graded patterns on Miura-ori can be exploited as a method to pre-program the out-of-plane curvatures. 18 Although the folding motion of the graded Miura-ori gets blocked when the panels are not allowed to deform, we found that a further folding results in a global in-plane bending and the panels undergo a nonrigid deformation. To the best of our knowledge, such deformation behaviors have not been reported so far.…”
Section: Introductionmentioning
confidence: 64%
“…17 It is recently known that the introduction of the graded patterns on Miura-ori can be exploited as a method to pre-program the out-of-plane curvatures. 18 Although the folding motion of the graded Miura-ori gets blocked when the panels are not allowed to deform, we found that a further folding results in a global in-plane bending and the panels undergo a nonrigid deformation. To the best of our knowledge, such deformation behaviors have not been reported so far.…”
Section: Introductionmentioning
confidence: 64%
“…A metamaterial is an artificially engineered material built up of unit cell entities that have physical properties that are beyond those of the constituent material itself [1,2]. Even though there is no exact definition for this class of materials, they exhibit unique physical properties on a macroscopic level, such as negative permittivity [3,4], negative magnetic permeability [5], negative Poisson's ratio [6][7][8][9], negative bulk modulus [10], negative density [10], etc. [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the significant potential for engineering design applications, researchers have recently explored the mechanical properties of kirigami-inspired structures. Similar to origami structures that fold the planar materials [ 25 ], kirigami-inspired structures are also capable of undergoing out-of-plane deformations. Isobe et al [ 1 ] investigated the mechanical response of the Kent paper and examined the relationship between the geometrical parameters of cuts and the resulting mechanical behavior.…”
Section: Introductionmentioning
confidence: 99%